2021
DOI: 10.1038/s41396-021-01123-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered metabolome and microbiome features provide clues in understanding irritable bowel syndrome and depression comorbidity

Abstract: Irritable bowel syndrome (IBS) is one of the functional gastrointestinal disorders characterized by chronic and/or recurrent symptoms of abdominal pain and irregular defecation. Changed gut microbiota has been proposed to mediate IBS; however, contradictory results exist, and IBS-specific microbiota, metabolites, and their interactions remain poorly understood. To address this issue, we performed metabolomic and metagenomic profiling of stool and serum samples based on discovery (n = 330) and validation (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Emerging evidence reveals that gut microbiota plays an important role in the pathophysiology of IBS. In alignment with other studies, our previous findings have reported significant changes in the structure of gut microbiota in patients with IBS, especially in IBS-D (Han et al, 2021; Jeffery et al, 2020; Zhao et al, 2020). Transplantation of fecal microbiota from IBS-D patients results in IBS-like symptoms including accelerated GI transit and intestinal barrier dysfunction in recipient germ-free mice (De Palma et al, 2017).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Emerging evidence reveals that gut microbiota plays an important role in the pathophysiology of IBS. In alignment with other studies, our previous findings have reported significant changes in the structure of gut microbiota in patients with IBS, especially in IBS-D (Han et al, 2021; Jeffery et al, 2020; Zhao et al, 2020). Transplantation of fecal microbiota from IBS-D patients results in IBS-like symptoms including accelerated GI transit and intestinal barrier dysfunction in recipient germ-free mice (De Palma et al, 2017).…”
Section: Introductionsupporting
confidence: 91%
“…Phenethylamine-producing bacteria analysis in IBS-D patients Metagenomics data of IBS-D patients and healthy volunteers were obtained as previously described (Han et al, 2021). Correlation analysis was conducted between serum 5-HT level and fecal PEA level with PEA-producing bacteria in IBS-D patients.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…Patients with IBS have a higher prevalence odd of migraine, while migraineurs with a long headache history and high headache frequency have a higher chance of being diagnosed with IBS [ 33 , 34 ]. The roles of intestinal microbiota and gut-brain axis may provide plausible explanations for migraine and its gastrointestinal comorbidities [ 5 ]. Host-microbiota interactions participate in various physiological and pathological events, including host homeostasis, energy metabolism, cognition, behavior and nociception [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional gastrointestinal disorders, including irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD), are common comorbidities of migraine [ 3 , 4 ]. These gastrointestinal disorders, together with extraintestinal comorbid neurological diseases, are linked to gut microbial dysbiosis [ 5 ]. Previous studies have demonstrated that the gut microbiota not only plays a key role in visceral pain, but also participates in the modulation of chronic pain [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irritable bowel syndrome is a common gastrointestinal disorder causing abdominal pain and irregular defecation, associated with changes in gut microbiota. In order to understand IBS depression comorbidity, Han et al [ 78 ] analyzed serum/fecal metabolome alterations related to microbiota in IBS patients. A quantity of 726 differentially abundant serum metabolites, including a cluster of fatty acyl-CoAs enriched in IBS, have been identified.…”
Section: Dysbiosis and Depressionmentioning
confidence: 99%